2013
DOI: 10.1038/ncomms3883
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33 regulates sterol regulatory element-binding protein 1 expression in mice

Abstract: MicroRNAs (miRs) are small non-protein-coding RNAs that bind to specific mRNAs and inhibit translation or promote mRNA degradation. Recent reports have indicated that miR-33, which is located within the intron of sterol regulatory element-binding protein (SREBP) 2, controls cholesterol homoeostasis and may be a potential therapeutic target for the treatment of atherosclerosis. Here we show that deletion of miR-33 results in marked worsening of high-fat diet-induced obesity and liver steatosis. Using miR-33−/−S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
165
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(190 citation statements)
references
References 46 publications
13
165
5
Order By: Relevance
“…However, the expression of miR-33a and several target genes were not perturbed in the liver, suggesting that the Srebf2 mutant allele did not disrupt miR-33a expression. Furthermore, the phenotypes of our mice did not recapitulate those of miR-33a-defi cient mice, which manifest hepatic steatosis and are prone to increased body weight on chow and high-fat diets ( 48 ). It is possible that miR-33a production is unaffected by our gene-trapped alleles or that there are compensatory changes in our mice that serve to maintain transcript levels for miR-33a target genes.…”
Section: Discussionmentioning
confidence: 81%
“…However, the expression of miR-33a and several target genes were not perturbed in the liver, suggesting that the Srebf2 mutant allele did not disrupt miR-33a expression. Furthermore, the phenotypes of our mice did not recapitulate those of miR-33a-defi cient mice, which manifest hepatic steatosis and are prone to increased body weight on chow and high-fat diets ( 48 ). It is possible that miR-33a production is unaffected by our gene-trapped alleles or that there are compensatory changes in our mice that serve to maintain transcript levels for miR-33a target genes.…”
Section: Discussionmentioning
confidence: 81%
“…A highly conserved miR, miR-33, is considered a potential therapeutic target for atherosclerosis because recent reports, including ours, [22][23][24][25] indicated that miR-33 has atherogenic effects by reducing high-density lipoprotein cholesterol (HDL-C) levels. 22,23,26,27 MiR-33 (or miR-33a in primates) is encoded by intron 16 of sterol regulatory element-binding factor 2 (SREBF2), a master regulator of sterol and fatty acid synthesis, and suppresses genes involved in cholesterol metabolism, such as ABCA1 and ABCG1 (ATP-binding cassette transporter A1 and G1) as target genes (primates including Homo sapiens also have miR-33b in the intron of SREBF1 in addition to miR-33a 28 ).…”
mentioning
confidence: 99%
“…This gene trap is also likely advantageous in that no region of the Srebf2 locus has been deleted to generate the null (or hypomorphic) alleles, and thus regulatory sequences and other important genes are less likely to be affected unintentionally. This is especially important because engineered mutations could affect the Srebf2 -embedded microRNA gene, miR-33, which represses Srebp1 and cellular cholesterol effl ux 33 ( 3 ).…”
mentioning
confidence: 99%